Co-Teaching Practices During Student Teaching - Stobaugh, Rebecca; Gichuru, Margaret (Educational (Re)naissance, 2017)
Accrediting organizations and regulations have compelled teacher preparation programs to establish partnerships with PK-12 schools to produce quality educators by utilizing effective teaching approaches such as co-teaching. The study examined co-teaching survey completed in the middle of student teaching. Data was collected from cooperating teachers and student teachers at different grade levels. The survey assessed participants' use of co-teaching strategies and the number of planning hours in each week. Pearson Correlations measured the relationship among the co-teaching strategies and the relationship between the co-teaching strategies and planning time. Results suggest there were more correlations among the co-teaching strategies for elementary student teachers. Three relationships were found in the middle school cooperating teachers data. Additionally, no correlations were found between any co-teaching strategies from either high school cooperating teachers or student teachers. The amount of planning time was shown to have no significant differences between any of the co-teaching strategies.